Polish Medical Doctors' Opinions on Available Resources and Information Campaigns concerning Antibiotics and Antibiotic Resistance, a Cross-Sectional Study - Olga Maria Rostkowska; Dorota Raczkiewicz; Weronika Knap-Wielgus; Wojciech Stefan Zgliczyński (MDPI AG, 2022)
Background: Antibiotic resistance (ABR) is at the top of global health threats. This paper aims to assess Polish physicians' readiness to impact ABR through prescribing routines. Methods: Surveying Polish physicians participating in specialization courses at the Center for Postgraduate Medical Education in Warsaw, Poland from October 2019 to March 2020. Results: Information was obtained from 504 physicians aged 25-59, mean 32.8 ± 5.9 years, mainly women (65%). Most doctors (78%) prescribed antibiotics at least once a week. Physicians indicated clinical practice guidelines as resources most often consulted in the management of infections (90%). However, clinical experience was also declared a powerful resource. In total, 54% of respondents recalled receiving information about the prudent use of antibiotics within 12 months, which partially translated into changing views (56%) and practice (42%). Physicians disagreed that national campaigns provide good promotion of prudent antibiotics use (75%) or that they are effective (61%). Only 40% of doctors were aware of the national campaign promoting responsible antibiotics use, 24% had heard about the European Antibiotic Awareness Day and 20% knew about the World Antimicrobial Awareness Week. Conclusions: Prescribers most often rely on clinical practice guidelines and their own experience as resources for antibiotics use. Doctors' awareness of available resources and information campaigns concerning antibiotics and antibiotic resistance should be improved.